Preparation method and application of copper-modified lignin carbon nanospheres
By combining solvent exchange method and hydrothermal treatment, transition metals and heteroatoms are doped and two-stage heating carbonization is carried out to prepare stable copper-modified lignin carbon nanospheres, which solves the size and size of lignin carbon spheres in the prior art. The problem of difficult morphology has been improved by improving the high active sites, hydrophilicity and electrochemical properties of the material.
Patent Information
- Application Number
- CN202411535111.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The existing hydrothermal treatment-carbonization method is difficult to accurately regulate the size and morphology of lignin carbon spheres, resulting in low hydrophilicity of the material and fewer active sites, limiting the application field of lignin carbon nanospheres.
Using a combination of solvent exchange method and hydrothermal treatment, copper-modified lignin carbon nanospheres with stable dimensional structure were prepared by transition metal and heteroatom doping and two-stage heating carbonization.
It improves the active site, hydrophilicity and pore structure of the material, enhances its electrochemical properties, and expands its application prospects in the fields of water treatment and electrochemistry.
Smart Images

Figure HDA0005111367500000011 
Figure HDA0005111367500000012 
Figure HDA0005111367500000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lignin application, and more specifically, relates to a preparation method and application of copper-modified lignin carbon nanospheres. Background Art
[0002] Lignin is the second most abundant natural polymer compound in nature, with the advantages of wide sources, low price and green renewable. Its molecular structure contains abundant benzene ring structures and active functional groups, with a carbon content of up to 60%, making it an ideal precursor for carbon materials. In the papermaking industry, tons of lignin are treated as waste (black liquor) or burned as low-grade fuel, which causes serious environmental pollution and waste of resources. Therefore, developing value-added uses of lignin and expanding its application areas are crucial for environmental protection and alleviating the energy crisis.
[0003] Lignin carbon nanospheres have great application prospects in the fields of energy storage, adsorption and catalysis due to their high specific surface area, high porosity and good stability. At present, the reported preparation methods of lignin carbon nanospheres mainly include direct pyrolysis, self-assembly-carbonization, cross-linking polymerization-carbonization, spray drying-carbonization, hydrothermal treatment-carbonization, etc. Among them, hydrothermal treatment-carbonization is a common method for preparing lignin carbon nanospheres, which usually dissolves lignin in an appropriate solvent, such as tetrahydrofuran, dioxane, etc., and then performs hydrothermal carbonization. However, although the common hydrothermal treatment-carbonization method can prepare spherical lignin carbon materials to a certain extent, the size and morphology of carbon spheres are affected by many factors such as hydrothermal temperature and hydrothermal time, which makes it difficult to accurately control and the material has low hydrophilicity and few active sites. It is difficult to meet the high demand for various functional materials, which limits the application field of lignin carbon nanospheres. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing copper-modified lignin carbon nanospheres in view of the deficiencies of the above-mentioned prior art. The present invention obtains lignin nanospheres with stable size and structure through solvent exchange method and hydrothermal treatment, and prepares copper-modified lignin carbon nanospheres through transition metal and heteroatom doping and two-stage temperature increase carbonization, which can be used for the degradation of water pollutants and aqueous zinc ion batteries, respectively, and have excellent degradation effect and electrochemical performance.
[0005] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0006] A method for preparing copper-modified lignin carbon nanospheres comprises the following steps:
[0007] (1) adding lignin to tetrahydrofuran to completely dissolve the lignin, and then adding deionized water at a constant rate with a peristaltic pump while continuously stirring to remove the tetrahydrofuran, thereby obtaining a light brown suspension; subjecting the suspension to a hydrothermal reaction in a reactor, and then centrifuging, washing, and freeze-drying to obtain lignin nanospheres;
[0008] (2) adding zinc nitrate and copper chloride to deionized water to obtain solution A; adding adenine to N,N-dimethylformamide (DMF) and heating until dissolved to obtain solution B; adding the lignin nanospheres described in step (1) to deionized water, and ultrasonically dispersing them uniformly to obtain solution C;
[0009] (3) adding solution B and solution C to solution A, stirring, centrifuging, and freeze-drying to obtain copper-modified lignin nanospheres;
[0010] (4) The copper-modified lignin nanospheres obtained in step (3) are mixed and ground evenly with potassium bicarbonate, and then calcined in a tubular furnace in two stages to obtain copper-modified lignin carbon nanospheres.
[0011] According to the above scheme, in step (1), the concentration of lignin added to tetrahydrofuran is 10-20 g / L; the volume ratio of tetrahydrofuran to water is 1:2-1:8; the hydrothermal reaction temperature is 150-180°C, and the time is 10-14 h; and a peristaltic pump adds deionized water at a constant rate of 10-20 mL / min.
[0012] According to the above scheme, in step (1), by controlling the concentration of lignin in the initial solution added to the tetrahydrofuran solution, lignin microspheres of different sizes can be prepared, and the larger the concentration, the larger the size of the spheres.
[0013] According to the above scheme, in step (2), the concentrations of zinc nitrate and copper chloride in solution A are 0.015-0.02 mol / L and 0.005-0.007 mol / L; the concentration of adenine in solution B is 0.03-0.05 mol / L, and the heating temperature is 50-100° C.; and the dispersed concentration of lignin nanospheres in solution C is 5-20 g / L.
[0014] According to the above scheme, in step (2), copper chloride is a precursor for transition metal doping, and adenine provides N doping, which can enhance the active sites and pore structure of lignin carbon nanospheres and improve the catalytic and capacitive properties.
[0015] According to the above scheme, in step (3), the stirring time after adding solution C is 12 to 14 hours, and the freeze-drying temperature is -40 to -60°C.
[0016] According to the above scheme, in step (4), the temperature of the two-stage calcination is 200-350°C and 600-900°C, and the time is 0.5-1.5h and 2-4h respectively; the mass ratio of copper-modified lignin nanospheres to potassium bicarbonate (KHCO3) is 1:0.8-1:5; the temperature is raised to the calcination temperature in a tubular furnace at a heating rate of 3-8°C / min. KHCO3 acts as an activator, which not only enhances the specific surface area of lignin carbon nanospheres during the calcination reaction, but also gives them a developed pore structure; and the first stage of low-temperature calcination is conducive to stabilizing the morphology of carbon nanospheres.
[0017] The copper-modified lignin carbon nanospheres (Cu-CNPs material) prepared by the above method can be used to degrade antibiotic pollutants in water bodies. The specific application method is: the Cu-CNPs material is added as a catalyst to antibiotic wastewater (i.e., antibiotic-contaminated water bodies), and after adsorption equilibrium, an activator potassium peroxymonosulfate (PMS) is added to achieve degradation of antibiotics in water bodies. Among them, PMS, as a commonly used Fenton-like oxidant, can directly react with antibiotics, but the efficiency is low. After adding Cu-CNPs as a catalyst, strong oxidizing active species can be generated, achieving high degradation efficiency of difficult-to-degrade antibiotics.
[0018] The copper-modified lignin carbon nanospheres (Cu-CNPs material) prepared by the above method can be used as a positive electrode material for aqueous zinc ion batteries. The specific application method is: the Cu-CNPs material is mixed with a conductive agent through a solvent and a binder, and then evenly coated on an aluminum foil and dried as a positive electrode, a zinc sheet is used as a negative electrode, and a zinc sulfate solution is used as an electrolyte to assemble an aqueous zinc ion battery. In the Cu-CNPs material of the present invention, Cu can improve the charge and discharge stability and energy density of the electrode material, and the heteroatom nitrogen introduced by adenine as a N source can also improve the overall capacitance of the material.
[0019] The present invention uses lignin as a carbon source, obtains lignin nanospheres with stable size and structure through solvent exchange method and hydrothermal treatment, and increases the active sites of the material, enhances the hydrophilicity, enriches the pore structure, and further improves the electrochemical performance through transition metal and heteroatom doping and two-stage temperature carbonization to obtain copper-modified lignin carbon nanospheres with stable morphology, and applies them to water treatment and electrochemistry. Compared with the prior art, the above technical scheme conceived by the present invention can achieve the following beneficial effects:
[0020] (1) Tetrahydrofuran is used as a solvent and the hydrothermal reaction temperature is controlled to prepare lignin nanospheres with stable size and structure, which have uniform appearance, regular morphology, good dispersibility, low preparation cost, simple process, and no need for complex chemical modification and long-term dialysis of lignin; then the lignin nanospheres are compounded with transition metal copper to further improve their electrochemical performance, and adenine is added to introduce nitrogen source to achieve subsequent heteroatom doping, increase the active sites of the material, and the prepared copper-modified lignin carbon nanospheres have the advantages of high specific surface area, many active sites, developed pore structure, good capacitance performance, etc., and have good application prospects in water treatment and electrochemistry. Specifically, the modified lignin carbon nanospheres described in the present invention are used as positive electrode materials for aqueous zinc ion batteries, have excellent specific capacitance at a current density of 1A / g, and have high power density and energy density; they are also used to treat antibiotic pollution in water bodies and have excellent degradation effects, and can be used to degrade a variety of antibiotic wastewater.
[0021] (2) The copper-modified lignin carbon nanospheres prepared by the present invention are environmentally friendly. Their application in aqueous zinc-ion batteries alleviates the dilemma of battery recycling to a certain extent, is beneficial to environmental protection, and also provides a new idea for solving the problem of low energy density and power density of energy storage materials. It also expands the application scope of lignin, realizes high value-added application of lignin, and has very significant resource and environmental value.
[0022] (3) The present invention adopts a two-stage calcination. During the calcination process, low-temperature carbonization is first performed to stabilize the original morphology of the material, and then high-temperature carbonization is performed to accelerate the activation and etching rate of the material by the activator, so that the prepared material has a rich pore structure and excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope image (SEM) of the Cu-LNPs material prepared in Example 1.
[0024] Figure 2 This is a scanning electron microscope (SEM) image of the Cu-CNPs material prepared in Example 1.
[0025] Figure 3 This is the X-ray photoelectron spectroscopy analysis chart (XPS) of the Cu-CNPs material prepared in Example 1.
[0026] Figure 4 This is the Raman spectrum (Raman) of the Cu-CNPs material prepared in Example 1.
[0027] Figure 5 The figure shows the change of tetracycline drug concentration over time when the Cu-CNPs material prepared in Example 1 degrades tetracycline drug under different pH conditions.
[0028] Figure 6 This is the battery cycle curve of the aqueous zinc ion battery assembled with the Cu-CNPs material prepared in Example 1. DETAILED DESCRIPTION
[0029] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the present invention is not limited to the following embodiments.
[0030] In the following embodiment, in step (1), the centrifugal speed is 4000-8000 rpm, and the time is about 5 minutes; in step (2), the stirring time of adding solution B and solution C to solution A is 12-14 hours, the centrifugal speed is 4000-8000 rpm, the time is about 5 minutes, and the freeze-drying temperature is -40 to -60°C.
[0031] Example 1
[0032] A method for preparing copper-modified lignin carbon nanospheres, the specific steps are as follows:
[0033] (1) 2 g of lignin was added to 100 mL of tetrahydrofuran to completely dissolve, and then 400 mL of deionized water was added at a constant rate using a peristaltic pump, and stirred continuously at room temperature for 12 h to remove tetrahydrofuran, to obtain a light brown suspension. The suspension was subjected to hydrothermal reaction at 160 ° C in a reactor for 12 h, and then centrifuged, washed with water, and freeze-dried to obtain lignin nanospheres.
[0034] (2) 3 mM zinc nitrate hexahydrate and 1 mM anhydrous cupric chloride were added to 160 mL of deionized water to obtain solution A; 8 mM adenine was added to 240 mL of DMF and heated at 70° C. and stirred until dissolved to obtain solution B; 1 g of lignin nanospheres obtained in step (1) was added to 100 mL of deionized water and ultrasonicated to obtain solution C.
[0035] (3) Solutions B and C were mixed and then added into solution A and stirred for 12 h. The mixture was centrifuged and freeze-dried to obtain copper-modified lignin nanoparticles (Cu-LNPs material).
[0036] (4) The product obtained in step (3) is mixed with potassium bicarbonate in a mass ratio of 1:1 and ground evenly, and then heated to 300°C in a tubular furnace at a heating rate of 5°C / min and kept warm for 1 hour, and then heated to 800°C at the same rate and kept warm for 2 hours to obtain copper-modified lignin carbon nanospheres (Cu-CNPs material).
[0037] Depend on Figure 1 It can be seen that before the two-stage calcination, the prepared copper-modified lignin nanospheres have regular morphology and uniform size, and their diameters are mainly concentrated in the range of 0.6 to 1.2 microns; Figure 2It can be seen that after the two-stage calcination, the nanospheres aggregated together, which was mainly caused by the agglomeration of the metal and also explained the successful loading of copper.
[0038] Depend on Figure 3 It can be seen that: through XPS analysis of electron binding energy, it can be concluded that the copper-modified lignin carbon nanospheres (Cu-CNPs) prepared in this embodiment are distributed with elements such as Cu, O, C, and N.
[0039] Depend on Figure 4 It can be seen from the Raman spectrum that I D / I G >1, indicating that the Cu-CNPs material prepared in this example has a higher disorder and defect degree, and can provide more active sites. When used as an electrode material, the greater the degree of defect of the material, the higher the cycle efficiency after the material is assembled into a battery.
[0040] Application Example 1
[0041] (1) The prepared tetracycline solution was used as the polluted water body, the concentration was 20 mg / L (i.e., 20 ppm), the pH value was between 3 and 11, the catalyst (i.e., the Cu-CNPs carbon material prepared in Example 1) was added at a concentration of 0.1 g / L, and the activator potassium monosulfate was added at a concentration of 0.2 g / L. Figure 5 As shown, when the Cu-CNPs material degrades tetracycline under different pH conditions, the concentration of tetracycline gradually decreases with time, confirming that the Cu-CNPs material has a higher response to tetracycline in a wider pH range, and the degradation effect is better when the pH is 7-9.
[0042] (2) The Cu-CNPs material prepared in Example 1 was used to remove tetracycline from water. The specific process was as follows: 0.1 g / L of the Cu-CNPs material (catalyst) prepared in Example 1 was added to 50 mL of 20 mg / L tetracycline solution and adsorbed for 30 min. After reaching adsorption equilibrium, 0.2 g / L of potassium peroxymonosulfate was added, and then the mixture was oscillated in a water bath at 25°C. After 60 min of degradation reaction, a tetracycline removal rate of 92.44% was achieved.
[0043] Application Example 2
[0044] Take a catalyst (Cu-CNPs material), a conductive agent (carbon black) and a binder (PVDF) in a mass ratio of 8:1:1, then mix them evenly with 1-methyl-2-pyrrolidone (NMP), evenly coat them on aluminum foil and dry them as the positive electrode, and use zinc sheet as the negative electrode and 1M zinc sulfate solution as the electrolyte to assemble an aqueous zinc ion battery. The battery cycle curve is as follows Figure 6As shown, after 5000 cycles at a current density of 10 A / g, the capacity retention rate is about 90%, and the Coulomb efficiency is close to 100%, confirming that the assembled zinc ion button battery has a stable operating voltage, high battery capacity and long life.
[0045] After the aqueous zinc ion battery was left to stand overnight, its electrochemical performance was tested using an electrochemical workstation. The button cell provided an excellent specific capacitance of 214.55F / g at a current density of 1A / g, and an energy density of up to 144.22Wh / kg.
[0046] Example 2
[0047] The difference between this embodiment and embodiment 1 is that in step (2), the mass of lignin nanospheres added to deionized water is 0.5 g.
[0048] The Cu-CNPs material obtained in this Example 2 was subjected to performance testing with reference to Application 1 and Application 2 of Example 1, and the results were as follows: 0.1 g / L of the Cu-CNPs material (catalyst) prepared in this Example 2 was added to 50 mL of 20 mg / L tetracycline solution and adsorbed for 30 minutes. After reaching adsorption equilibrium, 0.2 g / L of potassium peroxymonosulfate was added, and then the mixture was oscillated at a constant temperature in a water bath at 25°C. After 60 minutes of degradation reaction, a tetracycline removal rate of 81.93% could be achieved; the aqueous zinc ion battery was assembled, which provided an excellent specific capacitance of 150.55 F / g at a current density of 1 A / g, and an energy density of 92.21 Wh / kg.
[0049] Example 3
[0050] The difference between this embodiment and embodiment 1 is that the temperature of the hydrothermal reaction in step (1) is 180°C.
[0051] The Cu-CNPs material obtained in this Example 3 was subjected to performance testing with reference to Application 1 and Application 2 of Example 1, and the results were as follows: 0.1 g / L of the Cu-CNPs material (catalyst) prepared in this Example 3 was added to 50 mL of 20 mg / L tetracycline solution and adsorbed for 30 minutes. After reaching adsorption equilibrium, 0.2 g / L of potassium peroxymonosulfate was added, and then the mixture was oscillated at a constant temperature in a water bath at 25° C. After 60 minutes of degradation reaction, a tetracycline removal rate of 90.22% could be achieved; the aqueous zinc ion battery was assembled, which provided an excellent specific capacitance of 190.43 F / g at a current density of 1 A / g, and an energy density of 116.64 Wh / kg.
[0052] For those skilled in the art, the above description is only a preferred embodiment of the present invention. All modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention are within the protection scope of the present invention.
Claims
1. A method for preparing copper-modified lignin carbon nanospheres, characterized in that: The following steps are involved: (1) adding lignin to tetrahydrofuran and dissolving it uniformly, then adding water and stirring it uniformly, performing a hydrothermal reaction in a reactor, and then separating the solid product, washing it with water, and freeze-drying it to obtain lignin nanospheres; (2) adding zinc nitrate and copper chloride to solvent water to obtain solution A; adding adenine to N,N-dimethylformamide and heating until dissolved to obtain solution B; adding the lignin nanospheres described in step (1) to water and uniformly dispersing them by ultrasonication to obtain solution C; (3) adding solution B and solution C to solution A and stirring, separating the solid product and freeze-drying it to obtain copper-modified lignin nanospheres; (4) The copper-modified lignin nanospheres obtained in step (3) are mixed and ground evenly with potassium bicarbonate, and then calcined in a tubular furnace in two stages to obtain copper-modified lignin carbon nanospheres.
2. The method for preparing copper-modified lignin carbon nanospheres according to claim 1, characterized in that: In step (1), the concentration of lignin added to tetrahydrofuran is 10-20 g / L, the volume ratio of tetrahydrofuran to water is 1:2-1:8; the hydrothermal reaction temperature is 150-180° C., and the reaction time is 10-14 h.
3. The method for preparing copper-modified lignin carbon nanospheres according to claim 1, characterized in that: In step (2), the concentration of zinc nitrate in solution A is 0.015-0.02 mol / L, the concentration of cupric chloride is 0.005-0.007 mol / L; the concentration of adenine in solution B is 0.03-0.05 mol / L, and the heating temperature is 50-100° C.; the dispersion concentration of lignin nanospheres in solution C is 5-20 g / L.
4. The method for preparing copper-modified lignin carbon nanospheres according to claim 1, characterized in that: In step (3), after adding solution C, the continuous stirring time is 10 to 14 hours, and the freeze-drying temperature is -40 to -60°C; the volume ratio of solution A, solution B, and solution C is (150 to 180):(200 to 280):
100.
5. The method for preparing copper-modified lignin carbon nanospheres according to claim 1, characterized in that: In step (4), the temperatures of the two-stage calcination are 200-350° C. and 600-900° C., and the times are 0.5-1.5 h and 2-4 h, respectively.
6. The method for preparing copper-modified lignin carbon nanospheres according to claim 1, characterized in that: In step (4), the mass ratio of copper-modified lignin nanospheres to potassium bicarbonate is 1:0.8 to 1:5; the temperature is increased to the calcination temperature in a tubular furnace at a heating rate of 3 to 8°C / min.
7. Use of copper-modified lignin carbon nanospheres prepared by any method of claims 1 to 6 in treating water bodies contaminated by antibiotics.
8. The use according to claim 7, characterized in that: The specific application method is: after the copper-modified lignin carbon nanospheres are added as a catalyst into the polluted water body for adsorption equilibrium, an activator potassium peroxymonosulfate is added to achieve the degradation of pollutants in the water body; wherein, the copper-modified lignin carbon nanospheres are added at a concentration of 0.05 to 0.2 g / L in the polluted water body, and the activator is added at a concentration of 0.1 to 0.25 g / L in the polluted water body.
9. Use of the copper-modified lignin carbon nanosphere material prepared by any method of claims 1 to 6 in positive electrode materials for aqueous zinc ion batteries.
10. The use according to claim 9, characterized in that: The specific application method is: the copper-modified lignin carbon nanosphere material is mixed with a conductive agent through a solvent and a binder, and then evenly coated on an aluminum foil and dried as a positive electrode, a zinc sheet is used as a negative electrode, and a zinc sulfate solution is used as an electrolyte to assemble an aqueous zinc ion battery.